STRATEGI INTERNALISASI NILAI-NILAI AL-ISLAM PADA MAHASISWA DI RUSUNAWA UMSU - Pinem, Rasta Kurniawati Br.; Naimi, Nadlrah (Jurnal Ilmiah Al-Hadi, 2018)
The application of Islamic values ​​in life is something that cannot be negotiated, therefore the internalization of such values must be done and then these can be imprinted in themselves. Thus, Islamic values can be practiced in the daily life. College student is one of important element in building civilized society, and then they must be able to daily practice Islamic values. Therefore it is necessary to do maximum efforts in internalizing Islamic values in their life. This study focuses on how is the strategy to internalize the values ​​of Islam and Kemuhammadiyahan to student in UMSU dormitory. Data collection of this study was an interview and direct observation at the location. The study found that the internalization strategy that is carried out, namely: coaching of Quran reading, practical ibadah, studying of Islamic law and muahammdiyah values.